Energy efficiency of electric pulse installation based on a high-current plasma accelerator - Shanenkov I. I. Ivan Igorevich; Pak A. Ya. Aleksandr Yakovlevich; Sivkov A. A. Aleksandr Anatolyevich; Shanenkova Yu. L. Yuliya Leonidovna (2014, 2014)
Title screen